Genotyping and Beta–Lactamase Production of Escherichia coli Isolated from Different Sources - Mohammed Mahmood, Saja; Khalil Ibrahim, Suaad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
It was collected 145 samples from a variety of clinical sources, including urinary tract infections, wounds, blood, respiratory tract infections, stool, sputum, and high vaginal swabs, from various hospitals in Baghdad. Following the collection, we conducted microscopic examinations, biochemical examinations, and diagnosis. The Vitek-2 Compact System conducted the final analysis. It was gotten 50 isolates of Escherichia coli, and 34% of those were from urinary tract infections, wounds, respiratory system infections, sputum, and vaginal swabs. 72% of the isolates were from urinary tract infections, 14% were from wounds, and 2% were from respiratory system infections. Next, we conducted genotyping and tested for beta-lactamase resistance. It was genotyped bacterial isolates using the ERICPCR technique to understand their genetic relationships. The results showed three different patterns. We obtained (E19, E42, E50, E75) from each type, which consists of a group of isolates genetically related to each other on the genetic tree. We found genetic relatedness in isolates (E13, E140, E54, E30, E120, E60) that showed no genetic relatedness (E36, E38). Phenotypical detection revealed the presence of Extended-Spectrum B-Lactamase (ESBLS) beta-lactamase. The Double Disk Synergy Test (DDST) results revealed that E36, E13, E38, E120, and E60, with a percentage of 41.7%, possessed the ability to produce beta-lactamase, while E42, E50, E19, E30, E75, E140, and E54, with a percentage of 58.3%, lacked this ability.